Diventare grandi con il «Pioniere» (1950-1962) - Silvia, Franchini (Firenze University Press, 2006)
The conception and creation of the children's magazine "Pioniere" was an integral part of the extensive educational plan implemented by the PCI in the fifties for the construction of a new society. This book studies the issue of the dialogue set up with the young readers which evolved through a series of innovative initiatives, but was nourished above all by the post column run by the editor Dina Rinaldi. This was pivotal in the "education of feelings" and destined, in the optic of the "Pioniere", to the training up of the new generations. In Diventare grandi con il «Pioniere» viene studiato il tema del colloquio con i giovanissimi lettori cresciuto attraverso una serie di interventi innovativi, ma alimentato soprattutto grazie alla rubrica postale tenuta dalla direttrice Dina Rinaldi, centrale nell'«educazione dei sentimenti» destinata - nell'ottica del «Pioniere» - a formare le nuove generazioni. L'ideazione e realizzazione del giornalino per ragazzi «Pioniere» fece parte integrante del grande sforzo pedagogico compiuto dal PCI negli anni Cinquanta per la costruzione di una società nuova.